PEMBELAJARAN BERBASIS PROYEK DALAM PRAKTIKUM BIOLOGI TERHADAP KETERAMPILAN PROSES SAINS SISWA SMP MUHAMMADIYAH 6 PALEMBANG - Irham Falahudin; Muhamad Fauzi; winda purnamasari (Bioilmi: Jurnal Pendidikan, 2016)
This research about “Influence Project-Based Learning In Biology Lab to Process-Science Skills Of Junior High School of Muhammadiyah 6 Palembang. Project-based learning is a innovative model of learning, and more emphasis on contextual learning through activities complex. Science learning is currently lacking promoting science process skills ( KPS ), where as aspects of process science skills is the main basic of learning science in the laboratory. This research was conducted in Junior High School of Muhammadiyah 6 Palembang . This research aims to know the effect of project-based learning in biology lab about process science skills of junior high shcool of Muhammadiyah 6 Palembang. Population in this research is class VIII which number to 122 and the sample of 41 to use from class VIII.3. To measure the students process science skills to use instruments such as observation sheets , test and questionnaire . Testing the hypothesis of the research is based on analysis of simple regretion linear showed that there were significant effect at project-based learning in biology lab about process science skills with test F at standard 5% which Freg> Ftabel that is 15,90 > 4.10 and the average percentage of process science included in good categories. It can be concluded that the project-based learning in biology lab influencing process science skills of Junior High School Muhammadiyah 6 Palembang.